COMPARATIVE ANALYSIS OF GEODYNAMIC SETTINGS OF THE PERMO-TRIASSIC MAGMATISM IN EAST AND WEST SIBERIA - Al'mukhamedov A.I.; Medvedev A.Ya.; Kirda N.P. (My University, 1999)
A comparative analysis of the chemical composition of Permo-Triassic volcanics from the Siberian Platform and pre-Jurassic basement of the West-Siberian plate was performed to elucidate the geodynamics of magmatism in these regions. Two nearly coeval stages of magmatism (rifting and flood) have been established on the Siberian Platform. The rocks formed at the first stage are a differentiated series of basalts of elevated alkalinity; they occur in the paleorift structures of the northwestern and northern framings of the Tunguska syneclise. Volcanics of the second stage, an undifferentiated series of low-K tholeiites, are widespread throughout the lava plateau. When volcanics of both stages are present in the same section, the rocks of the first stage occupy the lower and middle parts of stratigraphic columns. The first systematic data on the composition of Permo-Triassic volcanics from the pre-Jurassic basement of the West-Siberian plate have shown that the most widespread rocks - tholeiitic and subalkalic basalts - are similar in geochemical composition to the rift-stage rocks of the Siberian Platform. The basement contains acid effusive rocks (rhyodacites and rhyolites), volcanics of the shoshonite-latite series, and a rift system, which completed its development in the Triassic. All this suggests rifting magmatism in this region. The geodynamics of magmatic activity in both regions is interpreted in terms of plume tectonics and related rifting with regard for the different thicknesses of lithosphere blocks in East and West Siberia and the kinematics of the movement of the consolidated Euro-Asian plate at the Permo-Triassic boundary.
Keywords: Triassic; Mesozoic::Triassic; Мезозой::Триасовая